Bridging Stakeholder Perceptions and Sustainability Reporting: A Comparative Systematic Review of Conventional and Sharia Banks in Indonesia - Tomy Rizky Izzalqurny; Tatas Ridho Nugroho; Adrian Hartanto Darma Sanputra; Heni Afitri (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2026)
Sustainability reporting (SR) in the banking sector is increasingly expected to demonstrate not only regulatory compliance but also credible accountability to stakeholders. However, in Indonesia’s dual banking system, there is limited systematic evidence on how SR shapes stakeholder perceptions differently between conventional and Sharia banks. This study examines the relationship between SR and stakeholder perceptions by comparing disclosure orientations, legitimacy mechanisms, and theoretical explanations across both banking systems. Using a Systematic Literature Review guided by the PRISMA 2020 framework and supported by Weighted Automated Text Analysis for Systematic Evaluation (WATASE), this study synthesizes nine peer-reviewed articles published between 2017 and 2024. The findings show that SR functions as a multidimensional accountability mechanism that strengthens transparency, stakeholder trust, and legitimacy. Conventional banks tend to frame SR in terms of ESG compliance, risk management, corporate governance, and investor confidence, reflecting an institutional legitimacy orientation. In contrast, Sharia banks integrate SR with Maqashid Syariah values, emphasizing justice, welfare, ethical stewardship, and moral accountability to build social and spiritual legitimacy. The theoretical integration of stakeholder theory, legitimacy theory, and Maqashid Syariah indicates that SR operates as both a governance instrument and a moral communication medium. This study contributes by developing a comparative accountability perspective that links SR quality, governance mechanisms, stakeholder trust, and legitimacy within Indonesia’s sustainable banking landscape. In practice, the findings offer insights for regulators and banking practitioners to harmonize ESG-based reporting with Islamic governance principles.